If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1x(8x+5)=12x(6x+1)
We move all terms to the left:
1x(8x+5)-(12x(6x+1))=0
We multiply parentheses
8x^2+5x-(12x(6x+1))=0
We calculate terms in parentheses: -(12x(6x+1)), so:We get rid of parentheses
12x(6x+1)
We multiply parentheses
72x^2+12x
Back to the equation:
-(72x^2+12x)
8x^2-72x^2+5x-12x=0
We add all the numbers together, and all the variables
-64x^2-7x=0
a = -64; b = -7; c = 0;
Δ = b2-4ac
Δ = -72-4·(-64)·0
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{49}=7$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-7)-7}{2*-64}=\frac{0}{-128} =0 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-7)+7}{2*-64}=\frac{14}{-128} =-7/64 $
| v−1=1+2v | | 12x-1+22x+4=180 | | 2(-3x+2)=11 | | -4p+9=−5- | | t=3t-5 | | -14=m-27 | | 3w+17=50 | | 0.50(3)+1(x)=0.75(3+x) | | –7+p=–6p | | 7+y-10=2y | | 5/3-x=7/9-x | | 3(x+6)=243 | | m-19=40 | | k/3-3=-3 | | (n)=n3+2n | | 0,5x-5=25 | | 3/c=3/10 | | 7x-1+2x=x+7 | | X+12=5(4-x) | | y=1/7(70) | | x2=1764. | | y = –5(10)+30 | | 13x+27x-1=180 | | 3n-5=5n-15 | | 6x-8-2x=x+7 | | –6f+10=–5f | | 2(x+3)+1=15+x | | 300=200xx1,5 | | -8=j/3-2 | | 90+(3x^2+60)+(2x^2-25x)=180 | | 1.83x+75=R | | x=4=-14 |